MICROBIOLOGICAL CHARACTERISTICS AND ANTIMICROBIAL RESISTANCE IN DIABETIC FOOT ULCERS - Yulia Ratna Dewi; Arum Kusuma Putri; Mutia Azahra (Tahta Media Group, 2026)
Background: Diabetic foot ulcers (DFUs) are among the most severe complications of diabetes mellitus, contributing significantly to morbidity, prolonged hospitalization, and lower-extremity amputations. Infection plays a critical role in the progression of DFUs, with diverse bacterial involvement and increasing antimicrobial resistance posing major challenges to effective treatment. Objective: This study aimed to review and synthesize current evidence on bacterial identification and antimicrobial resistance patterns in diabetic foot ulcers. Methods: A semi-systematic literature review was conducted using electronic databases, including PubMed, Scopus, ScienceDirect, and Google Scholar. The study selection followed PRISMA guidelines. A total of 130 articles were initially identified, of which 30 studies met the inclusion criteria after screening and eligibility assessment. Data were extracted and analyzed using a qualitative descriptive approach with narrative synthesis. Results: The findings revealed that diabetic foot infections are predominantly polymicrobial, with a higher prevalence of Gram-negative bacteria compared to Gram-positive organisms. The most frequently identified pathogens included Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. A significant proportion of isolates exhibited resistance to commonly used antibiotics, particularly penicillin, amoxicillin, and trimethoprim-sulfamethoxazole. Gram-negative bacteria demonstrated more complex resistance mechanisms, including extended-spectrum beta-lactamase (ESBL) and carbapenemase production. Multidrug-resistant (MDR) organisms were commonly reported, further complicating treatment strategies. Conclusion: Diabetic foot infections represent complex polymicrobial conditions with a predominance of Gram-negative bacteria and a growing burden of antimicrobial resistance. Accurate bacterial identification and antibiotic susceptibility testing are essential to guide targeted therapy and improve clinical outcomes. Continuous surveillance and rational antibiotic use are necessary to prevent the further spread of resistant pathogens.